Cost comparison of in-person and telehealth modalities for a suicide safety planning group intervention: interim results from the “Project Life Force” randomized clinical trial - Raciborski, Rebecca A.; Hamerling-Potts, Kyra K.; Mitchell, Emily L.; Sullivan, Sarah R.; Kapil-Pair, Nidhi; Landes, Sara J.; Jager-Hyman, Shari; Goodman, Marianne (Frontiers in Psychiatry, 2023)
Suicide prevention is a clinical priority for the US Veterans Health Administration. Evidence-based interventions, including developing a suicide safety plan, are recommended practices and are becoming more widespread. Adaptations to further augment safety planning include a manualized group intervention (Project Life Force, PLF) that combines safety planning with the teaching of skills to maximize use of the plan. A multi-year randomized controlled trial to test efficacy of PLF compared to treatment as usual is currently in progress. However, approximately a year into the2 study, in-person groups were converted to telehealth groups due to the COVID-19 pandemic. This study compares the per-veteran cost of PLF when delivered in-person versus by telehealth using preliminary trial data from the first 2.5 years of the trial. Cost to deliver PLF was obtained from the Veterans Health Administration's Managerial Cost Accounting data, which relies on activity-based costing. We found no significant differences in the average number of sessions or average group size between in-person and telehealth. However, the cost per group session was lower for the telehealth modality and this led to significant overall per-veteran savings. While efficacy data comparing from the two arms is still underway and we await the ongoing RCT results, our interim cost analysis highlights potential savings with the telehealth modality.